Multivalent Ligands with Tailor‐Made Anion Binding Motif as Stabilizers of Protein–Protein Interactions. (24th September 2019) - Bartsch, Lina; Bartel, Maria; Gigante, Alba; Iglesias‐Fernández, Javier; Ruiz‐Blanco, Yasser B.; Beuck, Christine; Briels, Jeroen; Toetsch, Niklas; Bayer, Peter; Sanchez‐Garcia, Elsa; Ottmann, Christian; Schmuck, Carsten
Abstract: Modulation of protein–protein interactions (PPIs) is essential for understanding and tuning biologically relevant processes. Although inhibitors for PPIs are widely used, the field still lacks the targeted design of stabilizers. Here, we report unnatural stabilizers based on the combination of multivalency effects and the artificial building block guanidiniocarbonylpyrrol (GCP), an arginine mimetic. Unlike other GCP‐based ligands that modulate PPIs in different protein targets, only a tetrameric design shows potent activity as stabilizer of the 14‐3‐3ζ/C‐Raf and 14‐3‐3ζ/Tau complexes in the low‐micromolar range. This evidences the role of multivalency for achieving higher specificity in the modulation of PPIs. Abstract : Increased interactions : A new ligand, which contains a guanidiniumpyrrol moiety, is introduced as a novel synthetic stabilizer of 14‐3‐3ζ/C‐Raf and 14‐3‐3ζ/Tau interactions, incorporating supramolecular principles and multivalence to address specific protein–protein interactions.